Profil Creative Thinking Siswa SMA di Lombok : Habits of Mind - Masiah, Masiah; Firdaus, Laras (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Creative thinking is one of the skills that every individual must master in the 21st century. Each person has a different level of creative thinking. Measurement of creative thinking needs to be carried out so that in the learning process teachers can determine the learning methods and models that will be intensified. The aim of this research is to describe the creative thinking of high school students in Lombok which was accessed through a questionnaire. This research is survey research. The sample determination method is convenience sampling. The respondents involved were 731 students spread across 14 high schools in 3 districts in Lombok. Data were analyzed descriptively with percentages. The research results show that the average creative thinking of high school students in Lombok is in the creative category. This research is part of preliminary research, and for further research this data is verified with a creative test.